Japan on the Silk Road
1 online resource.
Keywords: Japan on the Silk Road provides for the first time the historical background indispensable for understanding Japan's current perspectives and policies in the vast area of Eurasia across the Middle East and Central Asia. Japanese diplomats, military officers, archaeologists, and linguists traversed the Silk Road, involving Japan in the Great Game and exploring ancient civilizations.The book exposes the entanglements of pre-war Japanese Pan-Asianism with Pan-Islamism, Turkic nationalism and Mongolian independence as a global history of imperialism. Japanese connections to Ottoman Turkey, India, Egypt, Iran, Afghanistan, and China at the same time reveal a discrete global narrative of cosmopolitanism and transnationality. The global team of scholars brings to light Japan’s intellectual and political encounters with the peoples and cultures of Asia, in particular Turks and Persians, Hindus and Muslims of India, Mongolians and the Uyghur of Inner Asia, and Muslims in China. Contributors include: Ian Nish, Christopher Szpilman, Sven Saaler, Selcuk Esenbel, Li Narangoa, Komatsu Hisao, Brij Tankha, Erdal Küçükyalcın, A. Merthan Dündar, Katayama Akio, Miyuki Aoki Girardelli, Klaus Röhborn, Mehmet Ölmez, Banu Kaygusuz, Oğuz Baykara, and Satō Masako.